Patient‐reported symptom severity, interference with daily activities, and adverse events in older and younger women receiving chemotherapy for early breast cancer. Issue 6 (20th November 2020) - Nyrop, Kirsten A.; Deal, Allison M.; Chen, Yi Tang; Reeve, Bryce B.; Basch, Ethan M.; Wood, William A.; Shachar, Shlomit S.; Carey, Lisa A.; Reeder‐Hayes, Katherine E.; Dees, E. Claire; Jolly, Trevor A.; Kimmick, Gretchen G.; et al.
Abstract : Background: To the authors' knowledge, it is unknown whether patient‐reported symptom severity and symptom interference with daily activities differ between younger (aged <65 years) and older (aged ≥65 years) women receiving similar chemotherapy regimens for early breast cancer (EBC). Methods: Study participants rated 17 side effects of chemotherapy regimens currently in use in clinical practice (2014‐2019). Results: Of 284 women with EBC (stage I‐III), approximately 57% were aged <65 years and 43% were aged ≥65 years. For anthracycline‐based regimens, a higher percentage of younger women reported moderate, severe, or very severe (MSVS) hot flashes (49% vs 18%) ( P < .001). For nonanthracycline regimens, a higher percentage of younger women reported MSVS hot flashes (38% vs 19%) ( P = .009) and a lower percentage reported MSVS arthralgia (28% vs 49%) ( P = .005). With regard to symptom interference with daily activities, a higher percentage of younger women being treated with anthracycline‐based regimens reported MSVS hot flashes (32% vs 7%) ( P = .001) and myalgia (38% vs 18%) ( P = .02). For nonanthracycline chemotherapy, a higher percentage of younger women reported MSVS interference for hot flashes (26% vs 9%) ( P = .006) and lower percentages reported abdominal pain (13% vs 28%) ( P = .02). Overall, there were no significant differences noted among younger versus older patients with regard to hospitalizations (19% vs 12%; P = .19), dose reductions (34% vs 31%; P = .50), dose delays (22% vs 25%; P = .59), or early treatment discontinuation (16% vs 16%; P = .9546). Conclusions: Older and younger women with EBC who were treated with identical chemotherapy regimens generally experienced similar levels of symptom severity, symptom‐related interference with daily activities, and adverse events. Lay Summary: In this study, women receiving chemotherapy for early breast cancer rated the severity of 17 symptoms and symptom interference with their activities of daily living. Older (aged ≥65 years) and younger (aged <65 years) women who received identical chemotherapy regimens generally experienced similar levels of symptom severity, symptom‐related interference with daily activities, and adverse events. Abstract : In the current study, women receiving chemotherapy for early breast cancer rate the severity of 17 symptoms and symptom interference with their activities of daily living. Older (aged ≥65 years) and younger (aged <65 years) women who received identical chemotherapy regimens generally experienced similar levels of symptom severity, symptom‐related interference with daily activities, and adverse events.